Novel PRKAR1A mutation in Carney complex: a case report and literature review - Zheng, Huaqiang; Kang, Hong; Qiu, Yizhen; Xie, Liangxiao; Wu, Jinzhi; Lai, Pengbin; Kang, Jiapeng (Frontiers in Endocrinology, 2024)
Objective: Carney complex is a rare autosomal dominant syndrome that has been shown to be associated with inactivation due to PRKAR1A mutations. We revealed a novel PRKAR1A gene mutation in Chinese patient with Carney complex and review the literature to enhance understanding of Carney complex. Case presentation：A 23-year-old Chinese male patient with a family history cardiac myxoma was admitted to our Department of Endocrinology because of central obesity and hyperpigmentation. Physical examination revealed a maximum blood pressure of 150/93mmHg, a waist circumference of 102cm, a weight of 70kg, a height of 170cm, and a BMI of 24.22kg/m2. Additionally, there was spotty skin pigmentation on the lip mucosa, purple striae on the abdomen， thin skin on both legs, and visible veins. Blood examination revealed hypercortisolemia, decreased adrenocorticotropic hormone (ACTH) levels and failure to suppress cortisol with low and highdose dexamethasone suppression tests. Magnetic resonance imaging (MRI) scan revealed multiple small adrenal nodules and Retroperitoneal neurogenic tumor. Genetic testing showed a novel heterozygous mutation in exon 5 of PRKAR1A (c.500_502+8delAAGGTAAGGGC). The patient underwent resection of the right adrenal gland and retroperitoneal neoplasms in 2020. Postoperative pathology following the right adrenal gland resection showed nodular hyperplasia of the adrenal cortex. The pathology from the retroperitoneal tumor resection revealed spindle cell tumors rich in pigment and cells. The patient was diagnosed as Carney complex according to Stratakis CA in 2001 guidelines. After long-term follow-up, the patient's condition was stable, with weight loss, waist circumference reduction, significantly lower cortisol levels, and normal blood lipids. Conclusion : This case reported a Carney complex in a Chinese patient, characterized clinically by non-ACTH-dependent Cushing's syndrome, familial recurrent cardiac myxomas, psammomatous melanotic schwannoma (PMS) and skin and mucosal pigmentation. A novel subtype of PRKAR1A mutation was discovered, which may affect the characteristics of the PRKAR1A protein and contribute to the development of Carney complex.